The role of prophylactic cholecystectomy versus deferral in the care of patients after endoscopic sphincterotomy - Archibald, Jason D. (Canadian Medical Association, 2007)
INTRODUCTION: Prophylactic cholecystectomy (PC) is advised after ES and clearance of ductal calculi on the basis of a randomized controlled trial that showed a requirement for cholecystectomy in 36% of patients who defer surgery. Other studies suggest the cholecystectomy rate to be as low as 8%. METHOD: To determine the proportion of patients who deferred cholecystectomy and the outcome, we reviewed 870 consecutive patients who underwent endoscopic retrograde cholangiography and sphincterotomy; the gallbladder of 420 of these remained in situ. Patients were assigned to PC or deferred cholecystectomy (DC) groups. RESULTS: Cholecystectomy was deferred in 180 of 310 eligible patients. DC patients were significantly older (66.4 v. 49.8 yr) and sicker (according to the American Society of Anesthesiology [ASA] physiological status score) and had a significantly higher mortality rate than did PC patients. Deaths were principally cardiovascular and not biliary related. After a follow-up of 24.2 (< 1–82.3) months, eventual cholecystectomy was required in 46 (24.7%) DC patients at a mean of 6 months after ES. The subgroup undergoing eventual cholecystectomy was younger (57.6 v. 69.4 yr; p < 0.001) fitter (ASA score of 1.98 v. 2.26; p = 0.015) and more likely to have residual cholecystolithiasis than were those who continued deferral. Recurrent pancreatitis was more common in DC (30%) than in PC (4.8%) patients if pancreatitis was the indication for sphincterotomy. DISCUSSION: PC is advised for patients with residual cholecystolithiasis after ES. In patients with relative contraindications, the choice is balanced in favour of cholecystectomy if there is a history of pancreatitis and in favour of deferral if more than 6 months have elapsed since ES.